Religiusitas Jemaat Di Masa Pandemi Covid-19 Berdasarkan Teks Matius 22:37-40 - Agus Surya (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2021)
This study aims to see the picture of religiosity of GKE Sinta Kapuas congregation during the Covid-19 Pandemic based on Matthew Text 22:37-40. The method used is qualitative with techniques of collecting observation data, interviews, and documentation. The source of the informant is the deacon, the assembly, and the congregation of GKE Sinta Kapuas as many as 8 people. The results showed that the religiosity of the congregation of GKE Sinta Kapuas during the covid-19 pandemic was in the good category. This appears in the church's commitment to obey and love God with all his heart, with all his soul, and with all his mind. Then, the church's commitment to remain faithful to the belief in God's provider, by having a commitment in reading the Bible, living in prayer, worship, giving thanksgiving, living to do God's will and living in holiness, faithful in ministry, visiting people who are experiencing difficulties, and participating in service for others affected by the covid-19 pandemic. As for the obstacles in the implementation of religiosity of GKE Sinta Kapuas congregation during the covid-19 pandemic in the form of decreased intensity of the congregation in reading the Bible. This is due to the conditions and demands of the daily needs of the congregation that must be gardened and as a result of the economic impact that hit the congregation due to the covid-19 pandemic. Pandemi covid-19 menyebabkan ibadah tatap muka di jemaat GKE Sinta Kapuas terbatas. Kondisi ini berdampak pada religiusitas jemaat karena kurangnya ibadah bersama di gereja. Penelitian ini memiliki tujuan untuk melihat gambaran religiusitas jemaat GKE Sinta Kapuas di masa Pandemi Covid-19 berdasarkan Teks Matius 22:37-40. Metode yang digunakan ialah kualitatif dengan teknik pengumpulan data observasi, wawancara, dan dokumentasi. Sumber informan adalah diaken, majelis, dan jemaat GKE Sinta Kapuas sebanyak 8 orang. Hasil penelitian menunjukkan bahwa religiusitas jemaat GKE Sinta Kapuas di masa pandemi covid-19 dalam kategori baik. Hal ini nampak pada komitmen jemaat untuk taat dan mengasihi Tuhan yang diimplementasikan dengan tekun membaca Alkitab, hidup di dalam doa, ibadah, memberi persembahan syukur untuk gereja, hidup melakukan kehendak Tuhan dan hidup dalam kekudusan, setia dalam pelayanan, mengunjungi orang-orang yang mengalami kesulitan, serta berpartisipasi dalam pelayanan bagi sesama yang terdampak pandemi covid-19. Adapun kendala dalam implementasi religiusitas jemaat GKE Sinta Kapuas di masa pandemi covid-19 berupa menurunnya intensitas jemaat dalam membaca Alkitab. Hal ini disebabkan oleh kondisi dan tuntutan kebutuhan sehari-hari jemaat yang harus berkebun dan sebagai akibat dari dampak ekonomi yang melanda jemaat karena pandemi covid-19.